2012
DOI: 10.1093/rpd/ncr464
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT fluoroscopy and cone-beam CT-guided percutaneous transthoracic biopsy: comparison based on patient doses

Abstract: In this study, two different techniques used for image-guided percutaneous transthoracic needle biopsy have been compared in terms of patient dose: computed tomography (CT) fluoroscopy (performed on a Toshiba Aquilion 64), supplied with several multidetector CT (MDCT), and cone-beam CT (CBCT) (performed on a Philips Allura Xper FD20), supplied with a few C-arm flat-panel angiographic devices. Dose data (10 patients for each technique) have been collected, and organ doses and effective dose have been evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
12
1
Order By: Relevance
“…For CBCT-guided biopsies, the effective dose (expressed in mSv) was estimated from dose-area product (expressed in mGy cm 2 ), using the previously described conversion factor for the Allura Xper FD20 system (0.31 mSv Gy −1 cm −2 ) that was obtained from a separate phantom study [11].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CBCT-guided biopsies, the effective dose (expressed in mSv) was estimated from dose-area product (expressed in mGy cm 2 ), using the previously described conversion factor for the Allura Xper FD20 system (0.31 mSv Gy −1 cm −2 ) that was obtained from a separate phantom study [11].…”
Section: Data Collectionmentioning
confidence: 99%
“…In recent years a new, real-time needle guidance technique using C-arm cone-beam CT (hereafter CBCT) was developed that can be used to visualize under fluoroscopic guidance the needle trajectory from skin to target pulmonary lesions during interventional radiology procedures [6][7][8][9][10]. It has been suggested that the CBCT system, compared to fluoro-CT, facilitates the needle biopsy procedure and likely reduces radiation exposure of patient and operator [11][12][13][14][15]; however a direct comparison with evaluation of the advantages of CBCT over conventional fluoro-CT biopsy is not currently available [15]. In this study we aimed to compare the performance of CBCT-guided and fluoro-CT-guided TNB for diagnosis of malignancy of indeterminate lung nodules, and to assess the radiation exposure with the two procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation dose is naturally higher than with standard fluoroscopy. However, compared with complex punctures with standard multidetector computed tomography (MDCT), the radiation dose even might be lower in cone-beam CT-guided procedures as with the Uro Dyna-CT [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, CT fluoroscopy results in operator radiation as well. In addition, CBCT radiation dose to the patient is lower than conventional CT 19,20 . The radiation dose to the patient can also be reduced once operators become more familiar with the technology.…”
Section: Discussionmentioning
confidence: 99%